Penguatan Budaya Konsumsi Bertanggung Jawab melalui Pendidikan Kewarganegaraan Global bagi Pelajar SMA Negeri 10 Malang - Yunita, Primadiana; Killian, PM Erza; Pritasari, Mercusia (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The culture of irresponsible consumption among students poses a challenge to environmental and social sustainability. The lack of students' understanding of the relationship between consumption and global citizenship is a major issue. The Program for Strengthening Responsible Consumption Culture through Global Citizenship Education at SMA Negeri 10 Malang aims to increase students' awareness and understanding of sustainable consumption. The methods used include material presentations, interactive discussions, and evaluation through pre-tests and post-tests involving 33 students. The pre-test results showed an average score of 80.91, which increased to 87.88 in the post-test. This improvement indicates that the educational methods applied were effective in enhancing students' understanding. Challenges encountered include low student participation in discussions and a lack of initial understanding. To address these issues, interactive learning methods such as simulations and case studies should be implemented. School and parental support also play a crucial role in fostering a sustainable culture of responsible consumption. The results of this activity demonstrate that global citizenship education can be an effective strategy in shaping a younger generation that is more aware of their social and environmental responsibilities.